Characterizations of Principal n-Ideals in Terms of Relatively Normal Nearlattices - Raihan, MS (Journal of Bangladesh Academy of Sciences, 2010)
In this paper, we have characterized the principal n-ideals of relatively normal nearlattices which are generalizations of several results on relatively normal nearlattices. We have also shown that for a central element n, the set of principal n-ideals is relatively normal if and only if any two incomparable prime n-ideals of S are co-maximal. DOI: 10.3329/jbas.v33i2.4103 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 199-208, 2009